Protective Factors in Resilience of Aceh Tsunami Survivors - Santoso, Guritnaningsih A.; Suleeman, Julia (ANIMA Indonesian Psychological Journal, 2013)
Aceh in the northern part of Sumatra island - Indonesia has experienced the most severe destruction by tsunami in December 2004. This study aims to find out whether there are differences in the resilience of Acehnese young adults and late adolescent survivors, as well as to identify the protective factors underlying the resilience of Aceh young adult survivors. Quantitative and qualitative approaches were conducted to identify the resilience of tsunami survivors using the characteristics of resilience proposed by Wagnild (2009). Results showed that resilience score of young adults were higher than resilience score of late adolescents. The meaningfulness, equanimity, existential aloneness, and perseverance were growing to support the resilience of young adult survivors. Moreover, Aceh cultural values were also identified as protective factors contributing to the participants’ resilience. The implication of this study is important for the healing programs for the tsunami survivors. Aceh di bagian Utara pulau Sumatra-Indonesia telah mengalami kerusakan yang paling parah oleh tsunami Desember 2004. Tujuan studi ini adalah menemukan apakah ada perbedaan dalam daya pulih antara penyintas tsunami dewasa muda Aceh dan penyintas tsunami remaja akhir, demikian pula untuk mengidentifikasi faktor-faktor pelindung yang mendasari ketabahan para dewasa muda Aceh. Pendekatan kuantitatif maupun kualitatif dipakai untuk mengidentifikasi ketabahan para penyintas tsunami dengan mengacu pada karakteristik daya pulih yang dikemukankan oleh Wagnild (2009). Hasil-hasil menunjukkan bahwa skor daya pulih para penyintas dewasa Aceh lebih tinggi daripada skor daya pulih para penyintas remaja akhir. Kebermaknaan, ketenangan hati, kesendirian eksistensial, dan ketekunan bertumbuh untuk mendukung daya pemulihan para penyintas dewasa muda Selain itu nilai-nilai budaya Aceh juga diidentifikasi sebagai factor-faktor pelindung yang berkontribusi terhadap daya pemulihan para partisipan. Implikasi studi ini penting untuk program-progran penyembuhan para penyintas tsunami.